Anatomies of modern discontent - Henricks, Thomas S., author.
1 online resource (240 pages).
Keywords: This book provides an overview and analysis of the thought of figures across the human and social sciences on the character, causes, and consequences of discontent in modern societies. Exploring the important social and cultural conditions associated with modernity, it focuses on the contributions of thirty-eight prominent scholars from the late nineteenth and twentieth centuries ⁰́₃ philosophers, historians, and social scientists ⁰́₃ on the subject of discontent and social malaise, and individual and collective well-being. Thematically organised, this volume offers brief portraits of the lives and key ideas of these thinkers, leading towards a presentation of modernity as a ⁰́₈differentiated complaint⁰́₉. Reclaiming an important tradition in the human and social sciences that sees life in grand scale, that integrates personal affairs with social and cultural matters, and that dares people to recommit themselves to this broader vision of human involvement, Anatomies of Modern Discontent will appeal to readers across the social sciences and humanities, particularly those with interests in social theory, sociology and philosophy.